Plan De Negocio De la Empresa Filtros Bahía S.A.S. Destinada a Comercialización de Purificadores de Agua a Base de Ozono en la Ciudad de Santa Marta (2024)
This project begins with a main focus in which it seeks to satisfy the demand of the population that wants to improve the quality of water consumption in their homes, in this way different variables will be studied such as the viability of this project, if the need for this in the population, but mainly what contribution will result for society in the event that this project in formation meets a first-hand need in the population, and thus explain the way in which these purifiers made from components and layers of ozone act effectively for health and what wellbeing it provides for the quality of life and consumption of the population in this city. It should be noted that the company seeks its good name for the marketing of this highquality, efficient and easy-to-use product, in addition to its variety of references, which makes it potentially competitive in the market, and of great vitality for the community of Santa Marta. This will be distinctive from the others and at the same time iconic, consequently customer fidelity will be present.